Mind your right booklet: awareness on cyber defamation law & media / Suria Fadhillah Md Pauzi ... [et al.] - Md Pauzi, Suria Fadhillah; Mustapha, Musramaini; Ahmad Zaini, Azniza; Mohd Zaki, Suhanom; Awang Kader, Mohd Aidil Riduan (2021)
Defamation is an area of law that provides a civil remedy when someone's statement or words end up causing harm and injury to reputation of others. The statement tends to lower a person's reputation and dignity in the estimation of public generally which causes him to be shunned and avoided and exposed the claimant to be ridiculed by others. In Malaysia, defamation can be both a civil and criminal offence. For civil cases, the relevant legislation is the Defamation Act 1957 whereas criminal defamation is covered by Chapter XXI (Sections 499 to 502) of the Penal Code. The action of defamation is arising and becomes a highlight in media in recent year. The defamation suit filed by Fashion Valet and Duck group founder Vivy Yusof on June 15 2020 against alia Najwa Hassannuddin, an Instagram and Facebook user for instance, has caused uproar among the social media users. This project aims to impart knowledge on law of defamation to the target groups namely students and media personnels. The project also aims to evaluate the participant's understanding on this law. For the first phase, the project is applied to the university students from Universiti Teknologi MARA Cawangan Pahang. The booklet uses simple language without legal jargon for easy understanding and learning. A fun and simple game-related technique is also used explain the elements of defamation to the participants. This booklet is user friendly and easy to comprehend. It uses interactive practices to disseminate, deliver, and expose the participants with up-to-date legal knowledge on selected issues which is aligned with Malaysia education blueprint 2015-2025. In terms of its' potential for commercialization, the booklet can be used not only in an academic setting but also very beneficial to the community at large especially to the media personnel who is an easy target for a claim of defamation.